Benefits of Home-Based Exercise Training Following Critical SARS-CoV-2 Infection: A Case Report - Longobardi, Igor; Prado, Danilo Marcelo Leite do; Goessler, Karla Fabiana; Oliveira Júnior, Gersiel Nascimento de; de Andrade, Danieli Castro Oliveira; Gualano, Bruno; Roschel, Hamilton (Frontiers in Sports and Active Living, 2022)
In the current scenario, in which an elevated number of COVID-19 survivors present with severe physical deconditioning, exercise intolerance, persistent symptoms, and other post-acute consequences, effective rehabilitation strategies are of utmost relevance. In this study, we report for the first time the effect of home-based exercise training (HBET) in a survivor patient from critical COVID-19 illness. A 67-year-old woman who had critical COVID-19 disease [71 days of hospitalization, of which 49 days were in the intensive care unit (ICU) with invasive mechanical ventilation due to respiratory failure] underwent a 10-week HBET aiming to recovering overall physical condition. Before and after the intervention, we assessed cardiopulmonary parameters, skeletal muscle strength and functionality, fatigue severity, and self-reported persistent symptoms. At baseline (3 months after discharge), she presented with severe impairment in cardiorespiratory functional capacity (<50% age predicted VO2peak). After the intervention, remarkable improvements in VO2peak (from 10.61 to 15.48 mL·kg−1·min−1, Δ: 45.9%), oxygen uptake efficiency slope (OUES; from 1.0 to 1.3 L·min−1, Δ: 30.1%), HR/VO2 slope (from 92 to 52 bpm·L−1, Δ: −43.5%), the lowest VE/VCO2 ratio (from 35.4 to 32.9 L·min−1, Δ: −7.1%), and exertional dyspnea were observed. In addition, handgrip strength (from 22 to 27 kg, Δ: 22.7%), 30-s Sit-to-Stand (30-STS; from 14 to 16 repetitions, Δ:14.3%), Timed-Up-and-Go (TUG; from 8.25 to 7.01 s, Δ: −15%) performance and post-COVID functional status (PCFS) score (from 4 to 2) were also improved from baseline to post-intervention. Self-reported persistent symptoms were also improved, and Fatigue Severity Scale (FSS) score decreased (from 4 to 2.7) from baseline to post-intervention. This is the first evidence that a semi-supervised, HBET program may be safe and potentially effective in improving cardiorespiratory and physical functionality in COVID-19 survivors. Controlled studies are warranted to confirm these findings.